Pengaruh Model Pembelajaran Project Based Learning (PjBL) dalam Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) - Siti Marwah Nurmuffidah; Asep Dudi Suhardini; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. The learning process at SDIT Al-Maqom experiences difficulties in student learning activeness in history of islamic culture which still uses traditional or conventional methods. This research aims to determine the condition of active learning of class IV students at SDIT Al-Maqom before and after the implementation of the Project Based Learning (PjBL) learning model and the influence on this learning model. This type of research is quantitative with a quasi-experimental approach model. The results of this research show that 1) The condition of students' activeness before the Project Based Learning (PjBL) learning model was implemented has decreased, as can be seen from the observation sheet which is categorized as